2018
DOI: 10.1001/jamaoto.2017.3262
|View full text |Cite
|
Sign up to set email alerts
|

Association of Continued Preoperative Aspirin Use and Bleeding Complications in Patients Undergoing Thyroid Surgery

Abstract: IMPORTANCE No evidence exists to direct the management of preoperative aspirin (acetylsalicylic acid) use in patients undergoing thyroid surgery. Nevertheless, a considerable number of patients interrupt receiving aspirin therapy during the preoperative period to minimize bleeding complications despite the increased risk of experiencing major adverse cardiac events. OBJECTIVE To determine whether aspirin therapy continued preoperatively increases bleeding complications in patients undergoing thyroid surgery. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Generally, FNAC is considered to be more useful for differentiating between neoplastic and nonneoplastic lesions than for detecting malignancy [23]. However, some authors have not found any association between cytological features and histological diagnosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, FNAC is considered to be more useful for differentiating between neoplastic and nonneoplastic lesions than for detecting malignancy [23]. However, some authors have not found any association between cytological features and histological diagnosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical haematoma is an uncommon complication after thyroid surgery, occurring in 0.3-4.2% of cases [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. It mostly occurs in the rst 6 hours after the surgical procedure, while after 24 hours it is quite infrequent [31,33,34,36,41,42,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, there are only two studies that evaluate the impact of the continuation of antiplatelet medications during the perioperative period of thyroid surgery [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations